Curative‐intent radiotherapy for pediatric osteosarcoma: The St. Jude experience. Issue 8 (22nd April 2019) - Tinkle, Christopher L.; Lu, Jason; Han, Yuanyuan; Li, Yimei; McCarville, Beth M.; Neel, Michael D.; Bishop, Michael W.; Krasin, Matthew J.
Abstract: Background: Radiation therapy (RT) confers local tumor control and survival advantages in some patients with osteosarcoma, yet pediatric and adolescent and young adult (AYA) population studies are limited. Methods: Twenty‐eight patients treated with curative‐intent RT (median dose, 59.4 Gy; range, 40‐76 Gy) at our institution from 1990 to 2017 were retrospectively identified. Cumulative incidence (CIN) of local failure (LF) was estimated by Gray's method and overall survival (OS) by the Kaplan‐Meier method. Competing‐risk regression and Cox proportional hazards models determined predictors of outcome. Toxicity was reported according to CTCAE v4.0. Results: With a median follow‐up of 99.1 months in living patients, nine patients (32.1%) developed LF. Estimated CINs of LF with competing risk of death at 5 years for the entire cohort, patients at initial diagnosis ( n = 16), and recurrent/refractory patients ( n = 12) were 32.7% (95% CI, 16.0‐50.5%), 25.0% (95% CI, 7.3‐48.0%), and 43.8% (95% CI, 13.6‐71.0%), respectively ( P = 0.31). Estimated 5‐year OS was 42.6% (95% CI, 23.2‐62.0%), 54.6% (95% CI, 29.5‐79.6%), and 24.3% (95% CI, 0‐52.2%), respectively ( P = 0.15). No clinicopathologic features were significantly associated with LF, yet lack of chemotherapy or metastasis at the time of RT was independent significant prognostic factors of decreased OS. Eleven patients experienced RT‐related morbidity, with two grade 3 toxicities and no grade 4/5 events. Conclusions: Curative‐intent RT in pediatric and AYA patients was well tolerated and achieved a local tumor control rate of 75% in patients with primary disease. Local control rates were similar to those in primarily adult studies, with similar or lower doses.